The role of ligamentum teres tenodesis in the management of developmental dysplasia of the hip - Ahmed O.A.A.A. Allah; Ibrahim E.A.E. Abuomira; Amr A.E. Amr (Al-Azhar Assiut Medical Journal)
Background and aim The treatment of developmental dysplasia of the hip (DDH) is still challenging. New advanced techniques have improved our knowledge of the best way to prevent the recurrence of dislocation and minimize complications during early treatment. This study aims to assess the results of ligamentum teres tenodesis in the treatment of DDH. Patients and methods This was a prospective case series, single-blinded study, conducted at Orthopedic Surgery Department, Al-Azhar University Hospital, Assiut on 20 children with DDH through the anterior or anterolateral Smith-Petersen approach with creating tunnel from acetabular cavity to intrapelvic cavity then tightening of the passed sutured ligamentum teres with interosseous sutures in the iliac bone. Result The mean age was 21.63±7.1 months with 55% aged 10–20 months. Eighty-five percent of cases were female. Seventy percent were from urban areas, and 65% of surgery was performed on the right side. We found highly significant statistical differences between the studied cases (preoperative and postoperative after ligamentum teres tenodesis) as regards modified Harris Hip Score, which obtained the improvement of studied cases clinically with stable hip joint, acetabular index (AI) and Tonnis grade both obtain the radiological reduction and stabilization of the hip joint. All the studied cases had no avascular necrosis postoperatively. Conclusion Open reduction using ligamentum teres tenodesis is an effective treatment for DDH. The tenodesis of ligamentum teres maintains reduction stabilization and can also shorten the hip spica postoperative period from 3 months to 1 month.